Answer:
![\displaystyle \boxed{3x - 2y = -28}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/byx9jutlu6c0ec9fmao8rrkcylxbpwq65b.png)
Explanation:
y - 5 = 3⁄2(x + 6)
y - 5 = 3⁄2x + 9
+ 5 + 5
__________
y = 3⁄2x + 14
- 3⁄2x - 3⁄2x
________
−3⁄2x + y = 14 [We do not want mixed numbers\fractions in our standard equation, so multiply by the denominator to get rid of it.]
−2[−3⁄2x + y = 14]
![\displaystyle 3x - 2y = -28](https://img.qammunity.org/2020/formulas/mathematics/middle-school/g3jx7yfs8ml1ef8lyn1rw7ydolrowplkvv.png)
I am joyous to assist you anytime.